Acute Phorate Poisoning in a Flock of Sheep- A Case Report - Chandrashekaraiah, Girish Bekkare; Chinnaiah, Ravikumar; Karabasanavar, Nagappa Shivaning; Veeranna, Santhosh Moghalahally; Nagaraju, Pavankumar Kabberle; Narasimhaiah, Chandrashekhara (International Journal of Livestock Research, 2020)
Organophosphate compound pesticides represent one of the major classes of insecticides used in agriculture and animal husbandry in India. Among these, Phorate is one of the commonly used OPC compounds. A flock of Hassan breed sheep from a village near Hassan district, Karnataka, India was presented with history of severe mortality (61%) in a span of 2 days. There was circumstantial evidence of spraying of ragi straw with Phorate in fields for the control of termites. Clinical examination revealed watery salivation, tachypnoea, tachycardia, frequent urination, lacrimation, discharges from nostrils, dynpnoea, tremors, ataxia and pungent odour. The carcasses appeared bloated with congested conjunctival and oral mucus membranes, sticky lacrimal secretion and rectal prolapse. Microscopically, severe congestion and hemorrhoages was in urinary bladder in most of the animals. Other pathological changes were observed in liver, heart and spleen. Thin Layer Chromatography confirmed the presence of Phorate. The survived animals (n= 33) were treated with 2-PAM, Atropine Sulphate, parentral fluids and all ailing animals recovered from the OPC poisoning. This manuscript describes clinical, pathological and toxicological features of Phorate toxicity in a flock of sheep.